An IR for the Global South or a Global IR? (Guest Editorial) - Amitav Acharya (Global South Review, 2015)
The field of international relations (IR) is witnessing growing efforts to challenge Western centrism and give more space and voice to the Global South. These efforts are happening under a variety of labels, such as, but not limited to, non-Western IR, post-Western IR, Global IR, etc.To be sure, attempts to “bring the Global South in” by highlighting and generalizing from its contexts and challenges are not new. One could think of several examples, with Dependency theory and, somewhat later, Postcolonialism being two of the most prominent approaches. But recent efforts have been broader and targeted the entire discipline of IR, especially its major theories and concepts. And they have brought in a wider range of theoretical perspectives than Marxism and Postcolonialism, including Constructivism (Acharya), English School (Buzan) and even some realists (e.g. Mohammed Ayoob’s Subaltern Realism”).But labels overlap and can be confusing. Does post-Western subsume or exclude pre-Western or premodern, or pre-Westphalian histories and institutions? Are the distinctions between West and non-West meaningful? (They are increasingly blurred, but alas, the major IR theories are yet to reflect this)  What is the difference between “non-Western” and “post-Western”?